2013
DOI: 10.5267/j.msl.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigating different factors influencing job satisfaction: A case study of cement industry

Abstract: Job satisfaction plays an important role on increasing business productivity and efficiency. This paper presents an empirical investigation to study the relationship between job satisfaction and employees' personal characteristics including gender, marital status, etc. The proposed study designs a questionnaire and distributes it among 244 out of 800 employees who worked for cement industry in Iran. The data are analyzed using different statistical tests such as t-student and analysis of variance. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Job satisfaction plays an important role on the success of organizations. Shirvani et al (2013), for instance, presented an empirical investigation to investigate the relationship between job satisfaction and employees' personal characteristics including gender, marital status, etc. among employees who worked for cement industry in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction plays an important role on the success of organizations. Shirvani et al (2013), for instance, presented an empirical investigation to investigate the relationship between job satisfaction and employees' personal characteristics including gender, marital status, etc. among employees who worked for cement industry in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Eyvazi et al (2013) investigated the effects of human resource management on empowering employees in banking industry and reported that empowering employees could increase organizational commitment and Darvish et al (2013) confirmed the same results on other industry. Shirvani et al (2013) presented an empirical investigation to investigate the relationship between job satisfaction and employees' personal characteristics including gender, marital status, etc. by performing a survey among 800 employees who worked for cement industry in Iran.…”
Section: Introductionmentioning
confidence: 99%